Investigating First Language Acquisition of Indonesian Phonemes for Toddlers - Syahriah Madjid (Tamaddun Life, 2021)
This paper sheds light on the acquisition of Indonesian phonemes of a 2-year-old toddler in a natural setting. Data was obtained through qualitative approaches with the aim of investigating communication that occur in language acquisition (phonemes)for toddlers. The findings of the study revealed that in children aging 2 years, all vocal sounds can be pronounced precisely both in the initial, middle and end positions of the word, while consonant sounds there were still some that were not perfectly spoken. For example, phoneme /s/ if it is at the beginning and middle of a word, was pronounced /c/, and at the end position was pronounced /s/. Similar with consonant /l/. This sound can be pronounced perfectly if it is in the starting and final position of a word, in contrast to the middle position where the phoneme was not visible. The phoneme /r/ cannot be pronounced precisely at either the initial, middle or end position of the word.